Parametric Seismic Response of Base-Isolated Reinforced Concrete Silos - Portal, Piero H. (2025)
Silos are vulnerable structures during severe seismic events due to their slenderness and their interaction with stored material. This investigation presents the results of a special structure that incorporates a basal seismic isolation system, such as the Triple Friction Pendulum System (TFPS). A parametric study was conducted on eight models of reinforced concrete silos to evaluate the effectiveness of TFPS isolators in mitigating the effects of various parameters on their seismic response. This research makes significant contributions by identifying parameters that affect isolated silos, providing valuable insights into their seismic behaviour. The silos were modeled and validated by comparing the forces obtained from a modal spectral analysis with analytical forces from a previous study, achieving acceptable errors for the research objectives. Finally, a nonlinear dynamic time history analysis was performed using seven seismic records, selecting one as critical due to its peak acceleration at the start. The study determined that TFPS isolators efficiently reduced the influence of the analyzed parameters in slender silos, allowing their omission in non-critical seismic events for isolated structures. Compact silos exhibited reduced effectiveness due to uplift related to their compact design and the interaction between the stored material and the structure. This necessitates a thorough evaluation of the analysed parameters. In critical case, the full slender silo exhibited no increase in seismic response due to the stiffness contribution of the stored material. Conversely, empty slender silos showed increases because the force transfer in the final Phase of TFPS isolators became critical without the stiffness contribution of the stored material. Compact silos exhibited a similar seismic response for non-critical earthquakes, but the response was amplified due to significant lateral displacements.